The hidden bridge: Revealing how competitive advantage converts innovation capability into MSMEs’ performance - Ziedan, Emir; Darmawan, Baziedy Aditya (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2026)
Although micro, small, and medium enterprises (MSMEs) play a crucial role in the national economy, they continue to face significant challenges in maintaining their performance. Numerous prior studies have investigated innovation capability as the antecedent of business performance. However, those studies have predominantly concentrated on the direct relationship between innovation capability and business performance, leaving the understanding of how innovation capability translates into improved business performance remains incomplete. Moreover, the role of competitive advantage as the underlying mechanism on the innovation capability-business performance link in the context of MSMEs remains under-explored, highlighting the need for further investigation in this area. Therefore, this study aims to explore the role of competitive advantage as the mediation pathway of innovation capability in enhancing MSMEs’ performance by using the lens of dynamic capabilities perspective. Employing a survey, this study collected and used data from 159 MSMEs. The data were then analyzed using partial least squares-structural equation modeling (PLS-SEM) to assess the hypothesized relationships. The findings reveal that both innovation capability and competitive advantage serve as key drivers of MSMEs’ performance. Moreover, competitive advantage acts as a mediator, strengthening the impact of innovation capability on business performance. These results offer valuable insights for MSME practitioners, emphasizing the importance of fostering innovation-driven strategies and leveraging competitive advantage to sustain business growth and resilience in an increasingly dynamic market environment.